Le calcul et le politique - Stefan C. Aykut; Alain Nadaï (Revue d'anthropologie des connaissances)
Shortly after his election in 2012, French President F. Holland launched a major debate on French energy policy: the “Débat National sur la Transition Énergétique” (DNTE, 2012-13). This paper explores this process in order to address the making of this policy in France, and the articulation between calculation practices and political change. Political and calculation practices are approached as relational practices. The paper focuses on calculation practices and on their material support (models, scenarios, calculation tools), so as to analyse their role in the emergence of new political assemblages. In doing so, the paper discusses the changes in expertise (constitution, role), the transformations of public action (association / distance learning of actors), and the societal recomposition (productions, new collectives of actors) which the DNTE process brings forth. As a conclusion, we propose the notion of infra-model to discuss the tension between scientific robustness and mediation potential in the collective construction of visions of future.